Correction: Correction: Asymptomatic Plasmodium vivax malaria in the Brazilian Amazon: Submicroscopic parasitemic blood infects Nyssorhynchus darlingi. - Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0011429.].